The Relationship Between Bureaucratic School Structures and Teacher Self-Efficacy - Kilinç, Ali; Koşar, Serkan; Er, Emre; Öğdem, Zeki (McGill Journal of Education / Revue des sciences de l'éducation de McGill)

(untitled) (Faculty of Education, McGill University, 2016)
The purpose of this study was to examine the relationship between bureaucratic school structures and teachers’ self-efficacy. Participants included 252 teachers from 15 primary schools in Ankara, Turkey. Mean, standard deviation, correlation, and regression analyses were conducted. Results indicated that bureaucratic school structures and teacher self-efficacy were positively and significantly correlated and a bureaucratic school structure was a significant indicator of teacher self-efficacy. The results of the study are discussed with a focus on improving teacher self-efficacy.